French feminisms : gender and violence in contemporary theory - Allwood, Gill (Gender, change & society., 1998)
Explores theories of masculinity emerging from French feminist theories of gender, and from French feminist practice concerning violence towards women, highlighting both the commonalities and the specificities of the French case.